Polens illiberale Revolution - Müller, Klaus (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2018)
The recent populist wave that swept Eastern Europe put an end to the illusionary victory of liberal democracy across the region. This applies especially to Poland, the country with the most impressive civil society movement, Solidarnosz, and the frontrunner of radical market reforms. Despite the best economic performance of all post-communist countries, the populist party Law and Justice (PiS) came to power for a second time in 2015, only to impose its reactionary national-catholic model on the media, the law system, and the public sector. The success of PiS cannot be explained by the immanent strength of its populist rhetoric but points to the wilful neglect of its liberal predecessors of regional heterogeneity, precarious working conditions, and sharpened inequalities. While the electorate supports the valid points of PiS’s socio-economic programme, it is not inclined to follow its internally divisive and externally confrontational anti-EU ideology.